Formation of communicative culture of future heads of preschool institutions - Atroshchenko Tetyana (Borys Grinchenko Kyiv Metropolitan University, 2015)
Thе proposed article deals with the theoretical foundations of the communicative culture. It considers the requirements for speech manager that define his professional competence. Communicative culture of the future leader was defined as the ability to establish the right relationships, establish productive communication and interaction with the staff according to the requirements of modern pre-school education. The head of the preschool - a person who manages and within the institutions he is involved in the organization of management and has the primary responsibility to society for its effectiveness. The key to successful leadership is a combination of head and leader in one person. The challenges of the head of preschool institution are: to develop dynamic content of the educational process, increase its efficiency and quality, to promote innovative development. The modern manager must be competent both in matters of methodology training, education and development of preschool children, and in the management of the system. As part of the communicative culture, the speech culture of manager is expressed in perfect compliance of the rules of language, the ability to find accurate, clear, appropriate means to express his thoughts and feelings. Management team is called art, which achieved success in congenital managers, or those who are constantly working to improve management. Subject «Actual problems of preschool pedagogy» clarify the formation of communicative culture of future head of preschool institutions. It gives the opportunities to prepare students of the specialty 7.01010101 «Preschool Education» to their future job.